KUALITAS FISIK TELUR ASIN ITIK PEGAGAN YANG DIPROSES DENGAN MENGGUNAKAN ABU PELAPAH KELAPA SAWIT DAN ASAP CAIR - fitra yosi (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
Liquid smoke is a useful material for use in the process of preserving eggs. The purpose of this study was to determine the effect of the use of palm oil fronds ash and liquid smoke in the process of salting to the physical quality of pegagan duck’s egg. This study was assingned in a Completely Randomized Design, which consists of 5 treatments and 4 replications. Each replicatation used as much as 5 eggs. The treatment consists of R0, R1, R2, R3, and R4, where all of treatments used palm oil fronds ash and salt (1:0.25) and each treatment was added liquid smoke 0% (control), 2,5%, 5,0%, 7,5%, and 10% (v/v), respectively. The experimental variabel observed were egg weight loss, yolk and albumen weight, yolk and albumen index, egg shell weight, egg shell thickness, the depth of air cavity, yolk color, pH yolk adn albumen pH, Haugh units (HU), albumen viscosity. Data were subjected to analysis of variance and significantly different followed by Duncan's multiple range test at 5%. The results showed that the use of palm oil fronds ash and liquid smoke in the process of salting significantly affected (P < 0.05) the egg shell thickness, depth of air cavity, albumen weight, egg shell weight, albumen pH, albumen index, haugh units ( HU), albumen viscosity, and egg weight loss, but not significantly affected (P> 0.05) the yolk color, yolk pH, yolk weight, and yolk index. It was concluded that the use of palm oil fronds ash and liquid smoke in the salting process can maintain the physical quality of salted pegagan duck egg. (Key words: Liquid smoke, Palm oil fronds ash, Pegagan duck eggs, Physical quality)